Sustainable Projects by Local Governments in Turkey for Street Animals: An Evaluation and Forward- Looking Recommendations (Lex localis - Journal of Local Self-Government, 2024)
In Turkey, local governments provide services for the protection of stray animals through many different practices. The research analyses the sustainable practices and projects of local governments, which are legally considered to be the main responsible authorities, for stray animals and develops concrete policy recommendations for the future. In this context, the activities of the three largest local governments in Turkey, namely Istanbul, Ankara and Izmir, where a large part of Turkey's population lives, were analysed in detail. By applying to three major local governments from official sources, their activities for the protection of stray animals have been reached. In light of these data, very different practices and projects were encountered. Although the names of the practices and projects are different, it has been seen that the view of the problem of stray animals is the same. The research proposes an alternative application to the struggle of animals for life on the streets and the practices that support this struggle. This solution proposal is both more humane than existing projects and saves animals from the dangers on the streets. In addition, the suggestions are more sustainable than the existing projects.